Toolkit for exploring yield growth to 2050: Updating exogenous yield growth parameters in impact - Petsakos, Athanasios; Andrade, Robert; Rivera, Tatiana; Orozco, Esperanza; Suarez, Victor; Enahoro, Dolapo; Alene, Arega; Pedde, Valerien; Hareau, Guy (2024)
This toolkit is composed by guidelines, a manual, and example Power Point slides to update exogenous yield growth. The toolkit is expected to be used during the preparation and implementation of the expert consultations for review and updating of exogenous yield growth parameters to 2050 in the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) of the International Food Policy Research Institute (IFPRI). These exogenous yield growth parameters, commonly referred to as “Intrinsic Productivity growth Rates” (IPRs), represent a component of agricultural productivity that cannot be attributed to price effects, climate change and water shocks — elements which are explicitly captured by IMPACT. Yield growth from IPRs can represent, for example, new technologies, better management, improved input use efficiency, etc. Estimating IPRs to 2050 can be better understood as an exercise to derive future yield growth parameters from an informed extrapolation of observed past trends.